Stories with intent: a comprehensive guide to the parables of Jesus - Snodgrass, Klyne (William B. Eerdmans Publishing Company, 2018)
Stories with Intent offers pastors and students a comprehensive and accessible guide to Jesus' parables. Klyne Snodgrass explores in vivid detail the historical context in which these stories were told, the part they played in Jesus' overall message, and the ways in which they have been interpreted in the church and the academy. Snodgrass begins by surveying the primary issues in parables interpretation and providing an overview of other parables--often neglected in the discussion--from the Old Testament, Jewish writings, and the Greco-Roman world. He then groups the more important parables of Jesus thematically and offers a comprehensive treatment of each, exploring both background and significance for today. This tenth anniversary edition includes a substantial new chapter that surveys developments in the interpretation of parables since the book's original 2008 publication. - From publisher